2021
DOI: 10.1007/s00431-021-04242-5
|View full text |Cite
|
Sign up to set email alerts
|

High rate of clinically unrecognized SARS-CoV-2 infections in pediatric palliative care patients

Abstract: Little is known about the frequency and clinical course of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections in pediatric patients with severe comorbidities. In this prospective cross-sectional trial, the seroprevalence of SARS-CoV-2-IgG in patients with life-limiting conditions being treated by a large specialized pediatric palliative home-care team was determined. In order to gain insight into the infection chain, close contacts of seropositive patients were also included in the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It is curious that when considering those infectious‐related models of BCP‐ALL risk in relation to the COVID‐19 pandemic, both inflation and reduction in the ALL incidence are conceivable. On one hand, an infection with the severe acute respiratory syndrome coronavirus type 2 (SARS‐CoV‐2), very common in young children, 6 may directly act as trigger of the second hit. Single cases of BCP‐ALL shortly after SARS‐CoV‐2 infection may support this scenario.…”
Section: Childhood Acute Lymphoblastic Leukaemia and Sars‐c...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is curious that when considering those infectious‐related models of BCP‐ALL risk in relation to the COVID‐19 pandemic, both inflation and reduction in the ALL incidence are conceivable. On one hand, an infection with the severe acute respiratory syndrome coronavirus type 2 (SARS‐CoV‐2), very common in young children, 6 may directly act as trigger of the second hit. Single cases of BCP‐ALL shortly after SARS‐CoV‐2 infection may support this scenario.…”
Section: Childhood Acute Lymphoblastic Leukaemia and Sars‐c...mentioning
confidence: 99%
“…On one hand, an infection with the severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2), very common in young children, 6 may directly act as trigger of the second hit. Single cases of BCP-ALL shortly after SARS-CoV-2 infection may support this scenario.…”
mentioning
confidence: 99%
“…We found only one study directly relevant to children with life-limiting conditions; the authors analyzed the sera of 39 patients and found a 26% seroprevalence for SARS-CoV-2, but all seropositive patients were previously unrecognized despite severe comorbidities. 14…”
Section: Discussionmentioning
confidence: 99%
“…We found only one study directly relevant to children with life-limiting conditions; the authors analyzed the sera of 39 patients and found a 26% seroprevalence for SARS-CoV-2, but all seropositive patients were previously unrecognized despite severe comorbidities. 14 Some studies present a severe course of COVID-19, including death in children with underlying conditions. [5][6][7]15,16 In our study population, children with congenital malformations and chromosomal abnormalities most often suffered from COVID-19 and two patients from this group had a fatal outcome.…”
Section: What This Study Adds?mentioning
confidence: 99%